Pengaruh Penggunaan Media E-Booklet terhadap Minat Pengambilan Keputusan Penggunaan Kontrasepsi Pascasalin di UPTD Puskesmas Wanaraya Tahun 2025 - Juwai Emnestiningsih; Isnaniah -; Hapisah -; Rafidah - (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2026)
Abstract The use of postpartum contraception at the Wanaraya Community Health Center (UPTD Puskesmas Wanaraya) declined from 73.6% in 2024 to 29.4% in January–June 2025. One factor influencing the low use of postpartum contraception is mothers' lack of interest in decision-making. E-booklets are a means that can be used to increase the interest of pregnant women. This study was conducted to determine the effect of e-booklet media use on the interest in decision-making regarding postpartum contraception among pregnant women at the Wanaraya Community Health Center. This study used a pre-experimental design with a one-group pretest-posttest approach. The sample in this study consisted of 35 pregnant women in their third trimester, selected using total sampling technique. Data were collected using an interest questionnaire and analyzed using the Shapiro-Wilk test and Paired Sample T-Test. The results of the study show an increase in positive interest after the intervention, from 40% to 45.7%, while negative interest decreased from 60% to 54.3%. The average interest score increased from 35.45 to 39.60. The Paired Sample T-Test resulted in a p-value of 0.000 (p < 0.05), indicating that the use of e-booklets had a significant effect on increasing the positive interest of pregnant women in making decisions about postpartum contraception. Based on the research results obtained, it can be concluded that e-booklets have been proven to be effective in increasing positive interest in decision-making regarding postpartum contraception among pregnant women. Keyword: E-booklet, Interest, Postpartum Contraception, Pregnant Women.